2015
DOI: 10.1016/j.cmet.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin B Is a Secreted Hepatocyte Factor Linking Steatosis to Impaired Glucose Metabolism

Abstract: Liver steatosis is associated with the development of insulin resistance and the pathogenesis of type 2 diabetes. We tested the hypothesis that protein signals originating from steatotic hepatocytes communicate with other cells to modulate metabolic phenotypes. We show that the secreted factors from steatotic hepatocytes induce pro-inflammatory signaling and insulin resistance in cultured cells. Next, we identified 168 hepatokines, of which 32 were differentially secreted in steatotic versus non-steatotic hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
211
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(233 citation statements)
references
References 54 publications
19
211
0
3
Order By: Relevance
“…These investigators then showed both in in-vitro experiments and in mice that fetuin B impaired insulin action ex vivo in myotubes and in hepatocytes, and also caused glucose intolerance in-vivo in mice. As proof of concept that fetuin B was responsible for glucose intolerance in vivo, they then showed that silencing of fetuin B in the obese mice improved glucose tolerance in these animals [56]. Thus, these data strongly suggest that steatotic and inflamed liver is able to secrete a hepatokine that is capable of having an endocrine function beyond the liver to influence adversely glucose tolerance.…”
Section: Secreted Hepatokines and The Role Of Incretins And Glucagonmentioning
confidence: 87%
See 1 more Smart Citation
“…These investigators then showed both in in-vitro experiments and in mice that fetuin B impaired insulin action ex vivo in myotubes and in hepatocytes, and also caused glucose intolerance in-vivo in mice. As proof of concept that fetuin B was responsible for glucose intolerance in vivo, they then showed that silencing of fetuin B in the obese mice improved glucose tolerance in these animals [56]. Thus, these data strongly suggest that steatotic and inflamed liver is able to secrete a hepatokine that is capable of having an endocrine function beyond the liver to influence adversely glucose tolerance.…”
Section: Secreted Hepatokines and The Role Of Incretins And Glucagonmentioning
confidence: 87%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 Recent interest has also focussed on fetuin-B as a hepatokine that is capable of having an endocrine function beyond the liver to influence adversely insulin sensitivity and cause glucose tolerance. A recent study of 168 hepatokines, of which 32 were differentially secreted in steatotic versus non-steatotic hepatocytes showed that fetuin B was increased in humans with liver steatosis and in patients with type 2 diabetes [56]. These investigators then showed both in in-vitro experiments and in mice that fetuin B impaired insulin action ex vivo in myotubes and in hepatocytes, and also caused glucose intolerance in-vivo in mice.…”
Section: Secreted Hepatokines and The Role Of Incretins And Glucagonmentioning
confidence: 99%
“…The present study was, to the best of our knowledge, the first to explore the relationships between Fetuin-B and CKD. Studies from Meex et al [10] and Zhu et al [11] suggested a potential association between Fetuin-B and liver steatosis. We found that the highest level of serum Fetuin-B was significantly associated with the highest prevalence of NAFLD, and our unpublished data suggested that serum Fetuin-B level was also positively correlated with intrahepatic TG content.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-B, a kind of hepatokines, is known as the second member of the cystatin superfamily of cysteine protease inhibitors. Meex et al [10] reported that Fetuin-B was increased in humans with liver steatosis, impaired insulin action in myotubes and hepatocytes, and caused glucose intolerance in mice. Zhu et al [11] reported that serum Fetuin-B increased in subjects with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Проведено исследова-ние, в котором анализировались 168 гепатокинов, из ко-торых 32 секретировались гепатоцитами, пораженными при НАЖБП, и по его результатам сделан вывод, что фету-ин В был повышен у пациентов с НАЖБП и СД2 [32]. Эти-ми же исследователями показано в экспериментах in vitro и на мышах, что фетуин В ослабляет действие инсулина ex vivo в мышечных трубочках и гепатоцитах, а также вызы-вает толерантность к глюкозе у мышей in vivo.…”
Section: роль гепатокинов в развитии ирunclassified